1995
DOI: 10.1177/001872679504801003
|View full text |Cite
|
Sign up to set email alerts
|

Relationship on Work-Related Values of Singaporean and Japanese Managers in Singapore

Abstract: This study attempts to assess work-related values in Singapore and how these work values may differ from those of another nationality. The aim of this study is to replicate Hofstede's model in the Singapore managerial context. A comparison is made between Singaporean Chinese managers and Japanese managers in Singapore. Hofstede's four value dimensions of Individualism, Power Distance, Uncertainty Avoidance and Masculinity are used. The mean Power Distance and Masculinity scores of Singaporean Chinese managers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 15 publications
3
51
0
2
Order By: Relevance
“…That is, in such cultures a great importance is attached to predictable behavior (Kale & McIntyre, 1991), and variability in relationships is discouraged. Chew and Putti (1995) support this view by providing evidence that individuals high on UA values prefer to build relationships that are stable and enduring. Many past studies (Hambrick & Brandon, 1988;Laurent, 1983) investigate the relationship of UA values and managerial preference for stability/risk avoidance and posit that managers from high UA cultures have a high propensity for a stable and predictable organizational environment.…”
Section: Predictabilitymentioning
confidence: 75%
See 2 more Smart Citations
“…That is, in such cultures a great importance is attached to predictable behavior (Kale & McIntyre, 1991), and variability in relationships is discouraged. Chew and Putti (1995) support this view by providing evidence that individuals high on UA values prefer to build relationships that are stable and enduring. Many past studies (Hambrick & Brandon, 1988;Laurent, 1983) investigate the relationship of UA values and managerial preference for stability/risk avoidance and posit that managers from high UA cultures have a high propensity for a stable and predictable organizational environment.…”
Section: Predictabilitymentioning
confidence: 75%
“…Chew and Putti (1995) contend that high PD values promote duty-bound loyalties in relationships, and individuals who value hierarchy are less likely to develop feelings of affective attachment to targets, and they stay in existing relationships because of the perceived social appropriateness. Prior studies (Ryan & Deci, 2003) contend that practices such as submitting to authority tend to involve poor psychological functions of supporting one's well-being.…”
Section: Attractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, management practices and organizational culture are reflections of the national factors in terms of which the organizations were first found (Chew, 2000;Chew and Putti, 1995). More specifically, national culture is the most determinant factor in comparison to other national factors.…”
Section: Theoretical Framework and Relevant Studiesmentioning
confidence: 99%
“…This is reflected in many definitions of culture (Chew and Putti, 1995), and not surprisingly different disciplines define culture differently (Eagleton, 2000). Maull et al (2001) identified four views on culture in the organisational culture literature: as a learned entity, as a belief system, as strategy, and as mental programming (incorporating many elements of the previous three types).…”
Section: Culture and Tqmmentioning
confidence: 99%